Incidencia de un padre alcohólico en la estabilidad emocional de una adolescente de 14 años en la ciudad de Babahoyo - Calero Chimbo, Maria Isabel (2022)
Parents exercise one of the fundamental functions within the home, but the proper functioning is impaired when they use inappropriate behaviors that end up damaging the welfare of all members of the family system, including the one who exercises the negative actions. The present study has as its main objective to analyze the incidence caused by an alcoholic father in the emotional stability of a 14 year old adolescent girl from the city of Babahoyo; for the pertinent execution based on the clinical case, the tools for intervention and information gathering are considered by means of a mixed methodology that has methods and techniques such as: clinical method, semi-structured interview, direct observation, clinical history; it also has psychometric and projective batteries such as: the self-descriptive inventory of the adolescent to assess risk factors that may be affecting the emotional stability of the patient, the Beck anxiety inventory to measure anxiety levels, the Rosemberg self-esteem scale to verify feelings of personal worth, finally the Lands-Levy test drawing and history of an animal that allows to evaluate deep personality traits. It also has a wide bibliographic contribution according to the two variables proposed: alcoholic father and emotional stability. With the whole process applied, the structural diagnosis based on the criteria of the DSM-5 and ICD-10 manuals for a generalized anxiety disorder in adolescence F.98.80 was also presented, the reduction of the symptoms of the syndrome found was intervened by means of techniques of the cognitive-behavioral therapy approach.